MATEC Web of Conferences - Yurchenko physicist Professor of Tomsk Polytechnic University, Doctor of Technical Sciences; Serikov; Alkina; Neshina (2018)
In connection with the rapid development of telecommunications technologies, the provision of communication quality parameters and its reliability are very relevant. In this regard, the new approaches to the operation and control of telecommunications networks are required which are inconceivable without an integrated approach to solving this problem and developing a control system not only for the network state, but also for the quality indicators of its operation. The idea of the work is to develop the control system that is able to determine the principles of strict monitoring over the telecommunications network of Kazakhtelecom JSC in Karaganda. The analysis of the key performance indicators of the telecommunications network showed that after the implementation of the Network Management System hardware and software complex, all values of quality indicators meet the regulatory values. It allows monitoring and controlling the telecommunications network at various levels of operation of basic and auxiliary equipment in a wide range of work.